Publisher Correction: Global characterization of T cells in non-small-cell lung cancer by single-cell sequencing. (October 2018) - Guo, Xinyi; Zhang, Yuanyuan; Zheng, Liangtao; Zheng, Chunhong; Song, Jintao; Zhang, Qiming; Kang, Boxi; Liu, Zhouzerui; Jin, Liang; Xing, Rui; Gao, Ranran; Zhang, Lei; et al.
In the version of this article originally published, theP statistic described in Fig. 3d was incorrect. It was described as "P < 22 × 10–16 ". It should have been "P < 2.2 × 10–16 ". Also, the "CD8+ Treg" label in Fig. 4f was incorrect. It should have been "CD4+ Treg". The errors have been corrected in the HTML and PDF versions of this article.